El servicio multiflota y su incidencia en la gestión del control interno y del gasto en el proceso de abastecimiento de combustible de los vehículos de la municipalidad provincial de Trujillo, en los años comparados 2012-2013 - Rivas Huaripata, Renzo Gonzalo (2018)
The present research work, entitled "THE MULTIFLOTA SERVICE AND ITS INCIDENCE IN THE INTERNAL CONTROL MANAGEMENT AND THE EXPENSE IN THE FUEL SUPPLY PROCESS OF THE PROVINCIAL MUNICIPALITY’S VEHICLES OF TRUJILLO, IN THE PERIOD OF 2012- 2013", had as objective: Measure the incidence in the Internal Control management and fuel expense of the vehicles in the Provincial Municipality from Trujillo, through compliance evidence with the agreement with the Bank Multifunction Nation to allow a better control in the gas expense; This was done by using standards, reviewing management documents, applying surveys and interviewing officials and servers. The methodology used was: a) Selection of perception survey instruments and construction of the questionnaire of norms verification; b) Validation of the described instruments; c) Pilot testing of the instruments; d) Execution and development of the study, applying the instruments to the study population in order to obtain the perception of the subjects; and, e) Data analysis. The methods used were according to the nature of the qualitative variables of the present investigation, which corresponds to the observation, the content analysis and for the contrast of the hypothesis. Finally, as a result of the hypothesis testing, it is concluded that the level of internal control evaluation through the Trujillo Nation Bank Multiflota Service was a good tool to monitor the good use of fuel in the vehicles of the Provincial Municipality from Trujillo, and was associated with levels of compliance of the components of the internal control system in the management of the activities of the Provincial Municipality from Trujillo, consequently full compliance of standards are effective and therefore their activities are effective; With the Multiflota Service of the Nation Bank that influences the good Internal Control System